Nanoparticle-modified chitosan-agarose-gelatin scaffold for sustained release of SDF-1 and BMP-2 - Wang B (Dove Medical Press, 2018)
Bin Wang,1 Yuanwei Guo,2 Xiaofeng Chen,3 Chao Zeng,1 Qikang Hu,1 Wei Yin,1 Wei Li,1 Hui Xie,1 Bingyu Zhang,1 Xingchun Huang,1 Fenglei Yu1 1Department of Thoracic Surgery, The Second Xiangya Hospital of Central South University, Changsha 410011, People’s Republic of China; 2Center for Clinical Pathology, Affiliated to The First People’s Hospital of Chenzhou, University of South China, Chenzhou 432000, People’s Republic of China; 3Department of Anesthesiology, The Second Xiangya Hospital of Central South University, Changsha 410011, People’s Republic of China Background: Stromal cell-derived factor 1 (SDF-1) is an important chemokine for stem cell mobilization, and plays a critical role in mobilization of mesenchymal stem cells (MSCs). Bone morphogenetic protein 2 (BMP-2) plays a critical role in osteogenesis of MSCs. However, the use of SDF-1 and BMP-2 in bone tissue engineering is limited by their short half-lives and rapid degradation in vitro and in vivo. Methods: The chitosan oligosaccharide/ heparin nanoparticles (CSO/H NPs) were first prepared via self-assembly. Chitosan-agarose-gelatin (CAG) Scaffolds were then synthesized via gelation technology using cross-linked chitosan, agarose, and gelatin, and were modified by CSO/H NPs. The encapsulation efficiency and release kinetics of SDF-1 and BMP-2 were quantified using an enzyme-linked immunosorbent assay. A CCK-8 assays were used to evaluate biocompatibility of NP-modified scaffolds. The biological activity of the loaded SDF-1 and BMP-2 was evaluated using the transwell migration assay and osteogenic induction assay. An animal MSC recruitment model was used to study the ability of SDF-1 released from NP-modified scaffolds to induce migration of MSCs. Results: In this study, we developed a novel nanoparticle-modified CAG scaffold for the delivery of SDF-1 and BMP-2. CCK-8 assays demonstrated excellent biocompatibility of NP-modified scaffolds. In addition, we investigated the release of SDF-1 and BMP-2 from NP-modified scaffolds, and evaluated the effect of released SDF-1 on MSC migration. The effect of released BMP-2 on MSC osteogenesis was also examined. In vitro cell migration assays showed that SDF-1 released from NP-modified scaffolds retained its migration activity; osteogenesis studies demonstrated that released BMP-2 exhibited a strong ability to induce differentiation towards osteoblasts. Our in vivo recruitment assays showed continuous chemotactic response of MSCs to SDF-1 released from the NP-modified scaffold.Conclusion: The simplicity of synthesizing CSO/H NP-modified CAG scaffolds, combined with its high cytokine loading capacity and sustained release effect, renders NP-modified CAG scaffold an attractive candidate for sustained release of SDF-1 and BMP-2 to promote bone repair and regeneration. Keywords: cytokine delivery system, nanoparticles, chitosan-agarose-gelatin scaffold, stromal cell-derived factor-1, bone morphogenetic protein-2